Enlisting the Ixodes scapularis Embryonic ISE6 Cell Line to Investigate the Neuronal Basis of Tick-Pathogen Interactions - Mateos-Hernández, Lourdes; Pipová, Natália; Allain, Eléonore; Henry, Céline; Rouxel, Clotilde; Lagrée, Anne-Claire; Haddad, Nadia; Boulouis, Henri-Jean; Valdés, James J; Alberdi, Pilar; de la Fuente, José; Cabezas-Cruz, Alejandro; et al. (Pathogens (Basel, Switzerland), 2021)
Neuropeptides are small signaling molecules expressed in the tick central nervous system, i.e., the synganglion. The neuronal-like Ixodes scapularis embryonic cell line, ISE6, is an effective tool frequently used for examining tick-pathogen interactions. We detected 37 neuropeptide transcripts in the I. scapularis ISE6 cell line using in silico methods, and six of these neuropeptide genes were used for experimental validation. Among these six neuropeptide genes, the tachykinin-related peptide (TRP) of ISE6 cells varied in transcript expression depending on the infection strain of the tick-borne pathogen, Anaplasma phagocytophilum. The immunocytochemistry of TRP revealed cytoplasmic expression in a prominent ISE6 cell subpopulation. The presence of TRP was also confirmed in A. phagocytophilum-infected ISE6 cells. The in situ hybridization and immunohistochemistry of TRP of I. scapularis synganglion revealed expression in distinct neuronal cells. In addition, TRP immunoreaction was detected in axons exiting the synganglion via peripheral nerves as well as in hemal nerve-associated lateral segmental organs. The characterization of a complete Ixodes neuropeptidome in ISE6 cells may serve as an effective in vitro tool to study how tick-borne pathogens interact with synganglion components that are vital to tick physiology. Therefore, our current study is a potential stepping stone for in vivo experiments to further examine the neuronal basis of tick-pathogen interactions.
Keywords: Ixodes scapularis ISE6 cell line; synganglion; neuropeptides; Anaplasma phagocytophilum